Corporate disclosure and cost of equity : case of Malaysian listed companies - Mohd Waliuddin, Mohd Razali; Brahmana, Rayenda Khresna; Ganisen, a/l Sinnasamy (International Academy of Business and Economics, 2016)
Prior studies argue that company’s cost of capital significantly associated to the information asymmetry, and most of those research papers investigated develop countries. Malaysia, as an emerging market, offers its unique characteristic in terms of financial reporting regulation and is hugely influence by export-oriented companies. Therefore, this study purposely aims to examine whether information disclosure may affect the cost of equity capital of companies. We investigate this hypothesis by using all Malaysian listed companies excluding the finance, services, and utilities companies over 3 years period of 2010-2012. We use robust panel regression where the values are based on White robust standard errors that control for heterocedasticity errors. Overall, our findings support prior research that higher level of disclosure might discount the company’s cost of equity capital, suggesting that companies should disclose more information for better cost of capital.